Peran Ekonomi Digital Dan Ketenagakerjaan Dalam Mendorong Pertumbuhan Ekonomi: Studi 5 Negara Asean - Denita Capridasari (Jurnal Ilmu Ekonomi JIE, 2024)
The study aims to analyze the effect of internet network users, e-commerce transaction value, and total employment on economic growth. This research was conducted with a panel data regression approach and used secondary data from the World Bank and the data box. This study applies a panel data regression approach to analyze the effect of E-Commerce and energy absorption on the economic growth of 5 ASEAN countries in 2015-2021. The results confirm the hypothesis that the development of internet users has a positive impact on economic growth, the development of e-commerce value has a positive effect on economic growth, and the number of workers has a significant positive impact on economic growth.